2017
DOI: 10.1186/s12934-017-0630-z
|View full text |Cite
|
Sign up to set email alerts
|

Joining the in vitro immunization of alpaca lymphocytes and phage display: rapid and cost effective pipeline for sdAb synthesis

Abstract: BackgroundCamelids possess unique functional heavy chain antibodies, which can be produced and modified in vitro as a single domain antibody (sdAb or nanobody) with full antigen binding ability. Production of sdAb in conventional manner requires active immunization of Camelidae animal, which is laborious, time consuming, costly and in many cases not feasible (e.g. in case of highly toxic or infectious antigens).ResultsIn this study, we describe an alternative pipeline that includes in vitro stimulation of naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Recently, efforts has been made to develop in vitro selection of nanobodies against a target protein by for example cDNA display methods with synthetic or semi-synthetic libraries 22-25. Although some studies reported this method for selection of nanobodies against their target of interest, it must be mentioned that affinities were usually lower, in the range of 10 -7 to 10 -8 M, and that this approach demands large library sizes and sophisticated selection procedures, which currently is prohibitive for widespread implementation 26-28.…”
Section: Nanobody Structure and Development Platformsmentioning
confidence: 99%
“…Recently, efforts has been made to develop in vitro selection of nanobodies against a target protein by for example cDNA display methods with synthetic or semi-synthetic libraries 22-25. Although some studies reported this method for selection of nanobodies against their target of interest, it must be mentioned that affinities were usually lower, in the range of 10 -7 to 10 -8 M, and that this approach demands large library sizes and sophisticated selection procedures, which currently is prohibitive for widespread implementation 26-28.…”
Section: Nanobody Structure and Development Platformsmentioning
confidence: 99%
“…Detailed information on primer design, amplicon lengths and restriction enzymes used are presented in Supplementary Data Sheet 2 . Digestion of amplified PCR products, ligation into a pQE-30-mCherry-GFP plasmid (in-house modified vector pQE-30 UA, Qiagen Comor et al, 2017 , transformation and selection of clones were performed as described earlier Jimenez-Munguia et al, 2018 . Insertion of encoding genes was confirmed by sequencing with vector specific primers UA Insertom F and R (Supplementary Data Sheet 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…For library construction, B cells from naive or immunized camelids can serve as the point of departure, as can cultured camelid B cells exposed to antigens of interest (9). Purified proteins (10), cells or cell lysates containing antigens of interest (11,12), or recombinant DNA to induce antigen expression in the host (13,14) can serve as immunogens.…”
Section: Screening Platformsmentioning
confidence: 99%